A Traffic Equilibrium Model with Paid-parking Search. (1st July 2016) - van Nieuwkoop, Renger; Axhausen, Kay; Rutherford, Thomas
This paper describes a Wardropian traffic flow model, integrated with a search model for paid parking. The occupancy rate influences the probability of finding on-street (kerbside) or off-street (garage) parking spaces. We formulate the model as a mixed complementarity problem, which can be solved without a complete enumeration of all possible paths, and the use of readily available software. We analyse different parking policies in Zurich and find that changing the parking fee structure will lead to high efficiency gains. Incorporating household heterogeneity is not critical for the overall efficiency effects, but shows important regressive, distributional effects.